Mechanism of solid/liquid interfacial reactions. The maleic acid driven dissolution of calcite: An atomic force microscopy study under defined hydrodynamic conditions - Hong, Q; Suarez, M; Coles, B; Compton, R (1997)
The dissolution of calcite (CaCO3) in the presence of aqueous solutions containing maleic acid (cis-HOOC-CH=CH-COOH) in the pH range 4.3-8.2 has been studied by means of atomic force microscopy utilizing a flow cell of known hydrodynamics and modelable convection/diffusion. The latter permits the interpretation of dissolution rate data as measured by the z-piezo voltage in terms of a mechanism involving concentrations of solution species local to the dissolving crystal surface. In this way the dissolution mechanism for the (1014) cleavage plane is shown to proceed via reaction of the adsorbed monoprotonated anion, cis-HOOC-CH=CH-COO-, but to be inhibited by the adsorbed dianion, -OOC-CH=CH-COO-. Where available excellent quantitative agreement is noted with independent surface averaged kinetic data previously (J. Chem. Soc., Faraday Trans. 1 1989, 85, 4335) obtained using a channel flow cell.